Engineering geological evaluation of Bowa Dayole dam site, North Shewa Zone, Oromia, Ethiopia - Ashu Fekadu; Yadeta C. Chemeda; Shankar Karuppannan; Endalu Tadele Chala (Heliyon)
Developing nations like Ethiopia face food and water shortages due to weather and droughts. The Bowa Dayole masonry gravity dam is expected to irrigate farmland downstream. Despite this, the engineering geology is complicated by the presence of highly fractured and weathered aphanitic basaltic rock, along with a weak unwelded to welded tuff rock mass in the dam foundation. An engineering geological evaluation of the dam site and of the reservoir rocks and soils has addressed these challenges. Geological mapping, discontinuity surveying, core drilling, permeability testing, and laboratory analysis were used to achieve these goals. As the study area's main lithological units, geological mapping revealed units such as colluvial and alluvial deposits, aphanitic basaltic rock, and tuff units with varied degrees of fracturing and weathering. The unconfined compressive strength of these rocks' ranges from 0.16 MPa to 146.88 MPa, as determined from the Point Load Index Test, varying from very low to high strength. The Rock Quality Designation analysis indicated poor to excellent rock mass quality. The packer test revealed that the hydraulic conductivity with representative Lu values of less than 1 which indicated that excessive leakage at the dam site would not be expected. The allowable bearing capacity of aphanitic basaltic rock at the abutment and at the foundation was 0.54 MPa–6.77 MPa and 0.1 MPa–18.86 MPa, respectively. At the dam's foundation, tuff rock had an allowable load-bearing capacity of 0.037 MPa–0.11 MPa. Due to the poor bearing capacity of the tuff rock unit under the dam foundation, uniform settlement was expected, but even load distribution by the aphanitic basaltic rock and adequate foundation construction can mitigate this issue.